Determination of estrone and 17 beta-estradiol in human hair by gas chromatography-mass spectrometry - Choi, MH; Kim, KR; Chung, BC (ROYAL SOC CHEMISTRY, 2000)
An efficient procedure is described for the determination of estrone and 17 beta-estradiol in hair by gas chromatography-mass spectrometry (GC-MS). The method involves alkyloxycarbonylation with isobutyl chloroformate (isoBCF) of phenolic hydroxy groups after alkaline digestion of hair samples. The resulting isobutyloxycarbonyl derivatives of estrone and 17 beta-estradiol are extracted with hexane and subjected to chlorodifluoroacetyl derivatization in order to protect the remaining alcoholic hydroxy groups. When GC-MS with selected ion monitoring (SIM) was used, the quantitative ions were at m/z 270 and 384 in the electron ionization mass spectra for estrone and 17 beta-estradiol, respectively. The detection limits for SIM of the steroids were 1 and 2 pg, respectively, and the SIM responses were linear with correlation coefficients varying from 0.991 to 0.994 in the concentration range 0.2-4.0 ng g(-1) for the estrogens studied. The detection of estrone and 17 beta-estradiol in hair samples was possible in the concentration range of 0.24-1.30 ng g(-1). The concentrations of the two estrogens detected were different in male and female hair samples.
Keywords: ESTROGENS; DERIVATIZATION; METABOLISM; GROWTH